Pengaruh Abdominal Acupuncture Terhadap Penurunan Berat Badan Pada Klien Berat Badan Berlebih Di Griya Sehat Prima Hati Surakarta - Maria Dewi Christiyawati (Poltekkes Kemenkes Surakarta, 2017)
Abstract : Abdominal Acupuncture, Overweight. Overweight is a disorder characterized by accumulation of excess body fat tissue. Thuss it is necessary to be treated seriously. One of the most effective treatment for weight loss is acupuncture. Therefore the purpose of this study is to determine the effect of abdominal acupuncture method one of acupuncture method for weight loss in overweight clients. This method is a quasi –experimental research design with one group pre-post test design. The research is conducted in Griya Sehat Prima Hati Surakarta with 20 people as sample which obtained from total sampling. Data were analyzed by paired T-test with significance level of 0.05. The result of this research found that the average loss weight is 2,20 + 1,05 kg ( p < 0,05), which means that Ho is rejected and Ha is accepted. It can be concluded that there is an effect of abdominal acupuncture method to lose weight in overweight clients.